Drift-Diffusion Model parameterS Optimization - T. T. Trung; A. M. Borovik; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A new approach of nanoscale MOSFETs electrical characteristics calculating, the essence of which is the use of correction factors, as well as such values of classic drift-diffusion models, which would effectively take into account the quantum-mechanical transport mechanisms is proposed. Modified direct search method of drift-diffusion model optimization for MOSFET with a 90 nm channel length is developed and used.